Charting your career graph post residency - Monisha Mohan; Mini Mathew (Kerala Journal of Ophthalmology)
Overview on the opportunities available for an ophthalmology resident. Included are the options for those who want to start working immediately after PG and for those who want to do fellowships (both long term and short term.) both in India and abroad.